KESETARAAN HAK SERTA RESIKO KEKERASAN BERBASIS GENDER TERHADAP JURNALIS PEREMPUAN SUMATERA BARAT - oktarina, soraya; Syafriani, Desy; Fathiniah, Khafifah (Universitas Islam Negeri Imam Bonjol Padang, 2024)
The openness of the reform era and advances in communication, technology and information provide space for the media industry to thrive, from print, electronic to digital media. The press, an industry that opens up access for anyone, both men and women. Women take advantage of this to participate and choose the press as one of their employment options. As a result, the number of female journalists is increasing. However, regulations for the protection of female journalists have not been specifically created. Female journalists are often faced with obstacles and are even forced to struggle with the risk of gender-based violence. The research method used in this research is descriptive qualitative. The aim of the research is to look at the challenges faced by female journalists from West Sumatra in carrying out their profession, as well as the threat of gender-based violence they receive while working in the world of journalism. The research results show that there are a number of problems that female journalists in West Sumatra have to face. The matrilineal concept has two impacts, on the one hand, this culture is a reason for society to respect women, including the group of women journalists, on the other hand, it actually castrates women's freedom to mix in the masculine realm